2015
DOI: 10.1016/j.abb.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of the tyrosinase-catalyzed oxidative cyclocondensation of 2-aminophenol to 2-aminophenoxazin-3-one

Abstract: Tyrosinase(EC 1.14.18.1) catalyzes the monophenolase and diphenolase reaction associated with vertebrate pigmentation and fruit/vegetable browning. Tyrosinase is an oxygen-dependent, dicopper enzyme that has three states: Emet, Eoxy, and Edeoxy. The diphenolase activity can be carried out by both the met and the oxy states of the enzyme while neither mono- nor diphenolase activity results from the deoxy state. In this study, the oxidative cyclocondensation of 2-aminophenol (OAP) to the corresponding 2-aminophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Each metal‐ion‐binding site (A and B) contains three conserved histidine residues (Furumura et al, ; Lai et al, ). Together, they bind directly to the metal ions in mammalian TYRP1 (García‐Borrón & Solano, ) and fungal (Washington et al, ) TYR. The missense mutation (His214Asn) detected in our study disrupts one of those histidine residues interacting with a metal ion and is therefore expected to have a large negative effect on TYRP1 function.…”
Section: Discussionmentioning
confidence: 77%
“…Each metal‐ion‐binding site (A and B) contains three conserved histidine residues (Furumura et al, ; Lai et al, ). Together, they bind directly to the metal ions in mammalian TYRP1 (García‐Borrón & Solano, ) and fungal (Washington et al, ) TYR. The missense mutation (His214Asn) detected in our study disrupts one of those histidine residues interacting with a metal ion and is therefore expected to have a large negative effect on TYRP1 function.…”
Section: Discussionmentioning
confidence: 77%
“…There is a large difference between monophenolase activity and diphenolase activity, and reduced tyrosinase obviously has a lag phase when reacting with monophenol. These are important topics that need to be continuously explored and studied [ 11 ].…”
Section: Mechanism Of the Action Of Tyrosinasementioning
confidence: 99%
“…In addition, it plays an indispensable role in killing parasitic plants against phenolic symbiotic bacteria, the production of natural pigments and the synthesis of amino acid antibiotics such as lincomycin. The common point of these effects is inseparable from the tyrosinase using redox reactions with oxygen molecules [ 11 ].…”
Section: Function Of Tyrosinasementioning
confidence: 99%
“…It is reported that 2-aminophenoxazin-3-one (APO) core structure of bacterial products can be formed by oxidative coupling of two o-aminophenols catalyzed by various types of oxidases [32][33][34]. We therefore supplemented o-aminophenol to the Alteromonas sp.…”
Section: Purificatin and Structure Elucidationmentioning
confidence: 99%